Situation Report: Hungary, 31 March 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Catholic Bishops Deeply Concerned about Basic Communities Organized Vacations for Young Poles Continuing Commentary on the PCI-CPSU Dispute First Year of Contractual Operations Tourism: From the Spirit of Détente to the Spirit of Capitalism New Initiative in a Prominent Agricultural Cooperative